2017
DOI: 10.1039/c6md00618c
|View full text |Cite
|
Sign up to set email alerts
|

Regression of murine Ehrlich ascites carcinoma using synthesized cobalt complex

Abstract: Cisplatin as a chief chemotherapy has nephro-toxicity and so we have tried to develop a novel antitumor drug based on a combination of cobalt metal ion with an organic moiety. The antitumor activity of the complex was tested and against murine Ehrlich ascites carcinoma (EAC). Antioxidant capacity and nucleic acids content were determined. Cobalt(ii) diacetyl monoxime-2-hydrazinopyridine complex significantly diminished tumor load. It decreased the tumor proliferation rate and obviously increased the life span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
9
12
0
Order By: Relevance
“…Lalithadevi et al [35] declared that reduction of hepatic enzymes level in serum is one of the indications of the antitumor potential and treatment against tumor cells; they attributed the hepatoprotective effect of CLA to its isomers that induce cytotoxicity in hepatocytes or through its antioxidant property. The disturbance in liver and kidney function by tumor transplantation will consequently affect protein levels in blood of the experimental animals [46]. The significant decrease in total serum proteins and albumin, in the present study agrees with the results obtained by Saad et al [46] who also mentioned that in mice treated with EAC cells, total proteins, albumin percentages, and A/G ratios were decreased as compared to normal mice.…”
Section: Serum Proteinssupporting
confidence: 92%
See 1 more Smart Citation
“…Lalithadevi et al [35] declared that reduction of hepatic enzymes level in serum is one of the indications of the antitumor potential and treatment against tumor cells; they attributed the hepatoprotective effect of CLA to its isomers that induce cytotoxicity in hepatocytes or through its antioxidant property. The disturbance in liver and kidney function by tumor transplantation will consequently affect protein levels in blood of the experimental animals [46]. The significant decrease in total serum proteins and albumin, in the present study agrees with the results obtained by Saad et al [46] who also mentioned that in mice treated with EAC cells, total proteins, albumin percentages, and A/G ratios were decreased as compared to normal mice.…”
Section: Serum Proteinssupporting
confidence: 92%
“…The disturbance in liver and kidney function by tumor transplantation will consequently affect protein levels in blood of the experimental animals [46]. The significant decrease in total serum proteins and albumin, in the present study agrees with the results obtained by Saad et al [46] who also mentioned that in mice treated with EAC cells, total proteins, albumin percentages, and A/G ratios were decreased as compared to normal mice. In our previous study, the results confirmed clear anticancer activity for milk rich in CLA in both tumor cell lines (in vitro) and TTM (in vivo).…”
Section: Serum Proteinssupporting
confidence: 92%
“…In 1994, Kalavacherla et al [19] stated that malondialdehyde (MDA) evaluation seems to be a sensitive marker of inflammation in patients with rheumatoid arthritis. In fact, lipid peroxidation is involved in the pathogenesis of numerous diseases including hepato-cellular [20,21], renal [22] and cardiovascular diseases [23], diabetes [3], obesity [23] and cancer [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found significant decreases in RBCs count and Hb content in the ALI group suggesting a reduction of RBCs production by the induction of lung injury due to severe hypoxemia. Thus, the observed decreases in RBCs count and Hb content here may be explained by a suppressive effect on bone marrow erythropoiesis [ 19 ] that is potentially due to impairment in iron regulation due to inflammation. Besides, free radical intermediates may further speed up RBCs damage and disturb the erythropoiesis process.…”
Section: Discussionmentioning
confidence: 99%